2016
DOI: 10.1002/2015wr017990
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solution and computer program (FAST) to estimate fluid fluxes from subsurface temperature profiles

Abstract: This study details the derivation and application of a new analytical solution to the onedimensional, transient conduction-advection equation that is applied to trace vertical subsurface fluid fluxes. The solution employs a flexible initial condition that allows for nonlinear temperature-depth profiles, providing a key improvement over most previous solutions. The boundary condition is composed of any number of superimposed step changes in surface temperature, and thus it accommodates intermittent warming and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…FAST enables the user to convert a measured surface temperature time series into a multistep boundary condition (e.g., Figure a), perform the solution calculations (i.e., forward model from the initial condition), and infer the optimal groundwater flux by adjusting the flux to minimize the differences between calculated and measured temperature profiles. FAST has been applied to estimate fluxes from terrestrial borehole profiles in Japan (Kurylyk & Irvine, ), Australia (Irvine et al, ), and the Netherlands (Bense et al, ). In this study, FAST is applied to delineate transient and steady state zones (Figure c) for typical Darcy flux magnitudes using measured BWT variations, sediment temperature, and thermal conductivity.…”
Section: Methods: Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…FAST enables the user to convert a measured surface temperature time series into a multistep boundary condition (e.g., Figure a), perform the solution calculations (i.e., forward model from the initial condition), and infer the optimal groundwater flux by adjusting the flux to minimize the differences between calculated and measured temperature profiles. FAST has been applied to estimate fluxes from terrestrial borehole profiles in Japan (Kurylyk & Irvine, ), Australia (Irvine et al, ), and the Netherlands (Bense et al, ). In this study, FAST is applied to delineate transient and steady state zones (Figure c) for typical Darcy flux magnitudes using measured BWT variations, sediment temperature, and thermal conductivity.…”
Section: Methods: Thermal Analysismentioning
confidence: 99%
“…Heat is a natural groundwater tracer that is used to qualitatively or quantitatively study groundwater flow by capitalizing on the understanding that groundwater movement induces heat advection and influences subsurface thermal regimes (Anderson, 2005;Saar, 2011). Standard approaches rely on either steady state techniques, which infer groundwater fluxes from presumably static subsurface temperature-depth profiles (Bredehoeft & Papadopulos, 1965;Kurylyk et al, 2017;Shan & Bodvarsson, 2004), or transient techniques that estimate fluxes from the downward propagation of diel to decadal surface temperature changes (Goto et al, 2005;Hatch et al, 2006;Kurylyk & Irvine, 2016;Luce et al, 2013;Stallman, 1965;Taniguchi et al, 1999). A few studies have used transient thermal signals to trace groundwater in marine or coastal settings where tides, waves, and other hydrodynamic processes, coupled with variations in the surface energy budget, can create time-varying ocean temperature signals that penetrate into the shallow sediment (e.g., Befus et al, 2013;Goto et al, 2005;Wilson et al, 2016).…”
mentioning
confidence: 99%
“…However, profiles that are thermally disturbed by climate change must be analyzed with a transient method forced with a boundary condition to represent recent climate change. In contrast, computer programs (e.g., Kurylyk and Irvine 2016;Li et al 2019) specifically designed to automate solutions of transient numerical or analytical solutions for applying heat as a groundwater tracer are easier to implement. Although ground surface temperatures and surface air temperatures are often assumed to be coupled on a mean annual or decadal basis, studies have suggested changes to snowpack insulation or other nearsurface conditions may violate this assumption (Beltrami and Kellman 2003;Mann and Schmidt 2003;Smerdon et al 2006).…”
Section: Conclusion and Path Forwardmentioning
confidence: 99%
“…The solution also assumes steady-state conditions and neglects high-frequency and low-frequency temperature transience, which can lead to over-or under-estimates of Darcy fluxes in streambeds (Anibas et al, 2009) and in deep profiles (Ferguson & Woodbury, 2005;Irvine et al, 2016). However, the steady-state approach is attractive as it circumvents complicating issues associated with determining unknown initial conditions for deep profiles (Kurylyk & Irvine, 2016), as well as the need to run transient simulations. The steadystate approach is best suited to discharge zones where both the diel and seasonal temperature envelopes do not extend as deeply as in recharge zones, because the downward conduction is impeded by upward advection (Kurylyk, MacQuarrie, Caissie et al, 2015).…”
Section: Limitationsmentioning
confidence: 99%